2022
DOI: 10.3389/fpls.2022.843065
|View full text |Cite
|
Sign up to set email alerts
|

Plant Breeding for Intercropping in Temperate Field Crop Systems: A Review

Abstract: Monoculture cropping systems currently dominate temperate agroecosystems. However, intercropping can provide valuable benefits, including greater yield stability, increased total productivity, and resilience in the face of pest and disease outbreaks. Plant breeding efforts in temperate field crops are largely focused on monoculture production, but as intercropping becomes more widespread, there is a need for cultivars adapted to these cropping systems. Cultivar development for intercropping systems requires a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 229 publications
(306 reference statements)
0
36
0
Order By: Relevance
“…In the last years, breeding for more diverse crop systems (i.e. mixtures) has gained more attention (Bourke et al, 2021; Haug et al, 2021; Moore et al, 2022) and genes were identified which might be relevant for breeding in more diverse crop systems (Wuest et al, 2022; Wuest and Niklaus, 2018). Furthermore, a recent study found evidence for genetic and epigenetic evolution of monoculture and mixture ecotypes in grassland species (van Moorsel et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last years, breeding for more diverse crop systems (i.e. mixtures) has gained more attention (Bourke et al, 2021; Haug et al, 2021; Moore et al, 2022) and genes were identified which might be relevant for breeding in more diverse crop systems (Wuest et al, 2022; Wuest and Niklaus, 2018). Furthermore, a recent study found evidence for genetic and epigenetic evolution of monoculture and mixture ecotypes in grassland species (van Moorsel et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the commonly grown crops nowadays are bred for and multiplied in monocultures where they experience only intraspecific interactions and are thus not necessarily well suited to be grown in mixtures where also interspecific interactions occur. Hence, crop ecotypes specifically bred for mixtures might achieve additional yield benefits (Bourke et al, 2021; Brooker et al, 2021; Chen et al, 2021; Moore et al, 2022). Indeed, ecological studies conducted in grasslands have shown that plants adapt to growth in polycultures, with significant positive effects on community-level productivity (Zuppinger-Dingley et al, 2014) due to less intense competition in mixtures of adapted plants compared to the same mixtures of naïve plants (Schöb et al, 2018) – a result that could be confirmed in an annual crop system (Stefan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other multicrop systems described so far, intercropping involves more direct interactions among crop species. Therefore, in addition to the breeding goals described above, breeding programs focused on intercropping will select plants to enhance positive interactions (e.g., facilitation, niche differentiation) and reduce negative interactions (e.g., competition) among intercropping partners ( 39 ).…”
Section: Multicrop Breeding Targetsmentioning
confidence: 99%
“…However, how the specific microbial community of perennial crops forms little by little is still not fully understood. Perennial crops have their particularities, and many perennial plants are valuable economic crops, but perennial plants' diseases usually worsen over years of cultivation (Li et al, 2020 ; Moore et al, 2022 ). It is unclear whether the aggravation of plant disease during the development stages was associated with the succession of its rhizosphere microbial community, though.…”
Section: Introductionmentioning
confidence: 99%